Contemporary Fiqh Perspectives on Istihalah : A Case Study of Black Soldier Fly Larvae in Animal Feed Practices in Malaysia and Indonesia - Mohd Sham, Kamis; Nik Abdul Rahim, Nik Abdul Ghani; Luqman Hakim, Satiman; Siong Fong, Sim; Syed Ahmed, Abdallah (Faculty of Sharia, IAIN Metro, 2025)
This study explores the contemporary fiqh discourse surrounding the permissibility of using Black Soldier Fly (BSF) larvae as animal feed, focusing on applying the Arabic term istihalah within Islamic jurisprudence. Employing a qualitative research design, this study combines classical and modern textual analysis with field-based case studies. Data were gathered from BSF facilities such as Mega BSF Sdn. Bhd. in Sarawak, Malaysia, and findings were presented to religious authorities, including Pejabat Mufti Wilayah Persekutuan and Jabatan Mufti Perlis. Interviews with Islamic scholars and halal certification bodies were conducted, and thematic analysis was used to interpret the data. Findings show that classical Shafi'i jurisprudence requires total transformation (istihalah tammah) for impurity to become permissible. However, through laboratory-based biodegradation metrics and discussions with contemporary scholars, the study identifies increasing receptivity toward scientific indicators—such as microbial safety thresholds and substrate screening—as valid criteria for halal assessment. Furthermore, practices like istibra' (cleansing waiting periods) are reinterpreted using empirical microbiological tests. While some muftis remain cautious, others are open to harmonizing traditional principles with bioeconomic realities, particularly under the maqasid al-shariah framework. Academically, this study contributes a hybrid model of fiqh-science integration, offering a scalable framework for addressing similar cases where Islamic law intersects with emerging food technologies and sustainability practices.